Characterization and Photocatalytic Activity of CeO2-TiO2 for Photoreduction of CO2 to Methanol under Visible Light - Hamidah, Abdullah; Syarifah, Abd Rahim; Zahira, Yaakob; Khan, Maksudur R.; Nur Aminatulmimi, Ismail (2015)
A visible light-driven photocatalyst, CeO2-TiO2 catalyst was synthesized by impregnation method between TiO2 powder and cerium oxide nanoparticles slurry. The prepared catalyst samples were characterized by X-ray diffraction (XRD), UV-vis absorption spectroscopy and photoluminescence spectroscopy (PL). The band gap of CeO2-TiO2 catalyst was found to be 2.2-2.25 eV, which is significantly lower than the TiO2 catalyst (2.7eV). The band gap reduction clearly indicated the successful loading of CeO2 on TiO2 which was further confirmed by XRD. The photocatalytic activity was determined by measuring the photoreduction of CO2 to methanol in aqueous solution under visible light. The effect of cerium loading in the range of 0 to 5 wt% on the photocatalytic activity was studied and 2 wt. % CeO2-TiO2 was found to exhibit the maximum photoactivity of 18.6 μmol/g.catalyst after 6 hours irradiation. Results showed that the prepared photocatalyst is visible light active and may be used as effective catalyst in photoreduction of CO2 to methanol.